2023
DOI: 10.1212/wnl.0000000000207792
|View full text |Cite
|
Sign up to set email alerts
|

Association of Statin Use With Risk of Stroke Recurrence After Intracerebral Hemorrhage

David Gaist,
Luis Alberto García Rodríguez,
Jesper Hallas
et al.

Abstract: Background and Objectives Survivors of spontaneous intracerebral hemorrhage (ICH) may have indications for statin therapy. The effect of statins on the risk of subsequent hemorrhagic and ischemic stroke (IS) in this setting is uncertain. We sought to determine the risk of any stroke (ischemic stroke, IS or recurrent ICH), IS, and recurrent ICH associated with statin use among ICH survivors. Methods Using the Danish Stroke Registry, we identified all pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 43 publications
0
0
0
Order By: Relevance
“…8 9 Furthermore, large observational studies have shown neutral 10 or beneficial 11 effect of statins regarding the risk of ICH after stroke. 12 The risk of ICH might, however, depend on the statin intensity. 13 Statin intensity is largely determined early after an ischaemic event.…”
Section: Introductionmentioning
confidence: 99%
“…8 9 Furthermore, large observational studies have shown neutral 10 or beneficial 11 effect of statins regarding the risk of ICH after stroke. 12 The risk of ICH might, however, depend on the statin intensity. 13 Statin intensity is largely determined early after an ischaemic event.…”
Section: Introductionmentioning
confidence: 99%